PELAKSANAAN BIMBINGAN KELOMPOK DALAM MENGEMBANGKAN KETERAMPILAN BERKOMUNIKASI SANTRI PP AHLUSSUNNAH TERPADU KOTA LUBUKLINGGAU - Kardimin, Kardimin; Harmi, Hendra; Hartini, Hartini (CV. Lafadz Jaya, 2024)
The aim of this research is to describe, understand and identify the communication abilities and impacts of Integrated Ahlussunnah PP Santri Students in Lubuklinggau City. This research is qualitative research with data collection methods using observation, interviews, and documentation methods. The results of this research include: (1) The communication skills of the Integrated Ahlussunnah PP students in Lubuklinggau City are still relatively low. To improve communication skills, extra-curricular activities are held, such as OSIS, art performances, muhadloroh, PMR and so on, which also help build the communication skills of students at PP Ahlussunnah Terpadu Lubuklinggau City; (2) The implementation of group guidance at PP Ahlussunah Terpadu Lubuklinggau City is carried out once a week, with the stages of introduction, implementation, and evaluation. Group guidance is carried out using group discussion and question and answer methods, while the themes to grow students' courage in communicating are by giving tasks to be an MC, give a speech, tell a story (story telling), debate and organize and so on; and (3) The impact of group guidance on the communication skills of the Integrated Ahlussunnah PP students in Lubuklinggau City is very positive and significant.